ANALISA KINERJA RUAS JALAN JENDRAL SUDIRMAN DI SAMARINDA - DERIL, VIERNA PRATIWI (KURVA S JURNAL MAHASISWA, 2018)
Jendral Sudirman in Samarinda City is a secondary arterial road connecting primary and secondary areas to one another. Land use conditions contained in the Jenderal Sudirman street is dominated by public buildings with general activities of trade and offices. Jalan Jendral Sudirman in Samarinda is classified as Category III C class road. As the economy grows and the rising level of prosperity of the population will result in the increase of traffic levels. Traffic resulting from the need for transportation from the community, where people will always seek a faster, safer road and smoothly. The increase in population and the number of urbanization to urban areas will cause the movement and density, so the need for transportation also increases as well. On this basis, then do the research how the performance of Jl Sudirman street in Samarinda. In the Performance Analysis of Jalan Jendral Sudirman, the Road Manual Capacity Manual of Indonesia (MKJI'1997), which is described by Form UR-1 in the form of General and Geometric Condition of the road, UR-2 in the form of advanced input data ie Flow and Composition of traffic and Obstacles side, UR-3 in the form of Analyze the speed of free flow of light vehicles, Capacity and Speed of light vehicles. In the research of Performance Analysis of Jalan Jendral Sudirman, it is conducted a peak hour survey on Jl. Kinibalu to General Sudirman and Jl. General Sudirman to KH. Khalid and the survey was conducted at 6:00 to 9:00, 12:00 to 14:00, 16:00 to 18:00. After the calculation of the existing data, in segment I directions Jl. Kinibalu - General Sudirman is 1526.86 pcu / hr and service level is at level C, which means stable current zone, the driver in the limit chooses speed. Then the Segment II of General Sudirman Segment II General Sudirman - Kh, Khalid is 1396,92 smp / hour from standard <1600 smp / hour. (table 2.10) and Jurnal Transportasi 2 service levels are at level B. which means stable current zone, the driver has the freedom to choose speed